2007
DOI: 10.1016/j.neuropsychologia.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Visual elements of subjective preference modulate amygdala activation

Abstract: What are the basic visual cues that determine our preference towards mundane everyday objects? We previously showed that a highly potent cue is the nature of the object's contour: people generally like objects with a curved contour compared with objects that have pointed features and a sharp-angled contour. This bias is hypothesized here to stem from an implicit perception of potential threat conveyed by sharp elements. Using human neuroimaging to test this hypothesis, we report that the amygdala, a brain stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
284
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(329 citation statements)
references
References 34 publications
39
284
4
2
Order By: Relevance
“…From a methodological perspective, amygdala activation in response to rectilinear stimuli (43) has been observed with very brief presentation times (85 ms). In contrast, our participants viewed each stimulus for 3,000 ms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a methodological perspective, amygdala activation in response to rectilinear stimuli (43) has been observed with very brief presentation times (85 ms). In contrast, our participants viewed each stimulus for 3,000 ms.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, we hypothesized that the reverse contrast (i.e., rectilinear-curvilinear) would activate the amygdala. This specific prediction was derived from an earlier fMRI study in which it was shown that viewing rectilinear everyday objects activated the amygdala, suggesting that sharpness might serve as an early warning signal for potential danger (43).…”
mentioning
confidence: 90%
“…Low-level stimuli features of works of art trigger our attention, including shapes and tones, and other features such as symmetry and beauty [108][109][110][111][112][113][114]. Besides, the arts push boundaries, surprise, reveal, and excite both artist and spectator.…”
Section: The Arts Hypothesismentioning
confidence: 99%
“…The discipline 'neuroaesthetics' studies these low-level perceptual processes and how they relate to aesthetic preferences [115][116][117]. In this endeavour, neural structures of reward and pleasure have been found to be engaged during aesthetic experiences [107,111,[118][119][120].…”
Section: The Arts Hypothesismentioning
confidence: 99%
“…Arousal decreased and pleasure increased as greyscale colours changed from black through grey to white. Research has also identified hedonic perceptions of shape and contour, finding that people have a consistent preference for curved over pointed objects [3,18], possibly due to the inherent "threat" conveyed by sharp objects [4].…”
Section: Related Researchmentioning
confidence: 99%